2020
DOI: 10.3390/vaccines8040629
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Prices: A Systematic Review of Literature

Abstract: Vaccines are among the most vital interventions to control and reduce the morbidity and mortality worldwide. In accessing vaccines, pricing is usually the single most important deciding element. However, there is a scarcity of the literature on the vaccines pricing. The current study aims to review vaccine prices from the published literature and to evaluate factors that impact the pricing of vaccines. The literature (from 2015–2020) was reviewed to identify the original research articles. Systematic searches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…We identify vaccine price as the largest cost driving the cost-effectiveness of a maternal PPV. This finding aligns with previous studies on the cost-effectiveness of new and underused vaccines, such as human papilloma virus (HPV), in low-income settings [40, 41].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We identify vaccine price as the largest cost driving the cost-effectiveness of a maternal PPV. This finding aligns with previous studies on the cost-effectiveness of new and underused vaccines, such as human papilloma virus (HPV), in low-income settings [40, 41].…”
Section: Discussionsupporting
confidence: 91%
“…We identify vaccine price as the largest cost driving the cost-effectiveness of a maternal PPV. This finding aligns with previous studies on the cost-effectiveness of new and underused vaccines, such as human papilloma virus (HPV), in low-income settings [40,41]. The implementation of a cost-effective maternal pneumococcal vaccine would require negotiations with vaccine suppliers on vaccine price.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prices of HPV vaccines were declined with the passage of time due to many reasons, e.g. competitive tendering of prices [27,28], the involvement of organizations, such as the Global Alliance for Vaccine [27,28], and having more suppliers more competition [27]. The affordable prices of vaccines could be achieved through tender procedures because vaccine pricing is affected by contract volume and its duration, country, per capita gross domestic product (GDP), and the number of offers received [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…competitive tendering of prices [27,28], the involvement of organizations, such as the Global Alliance for Vaccine [27,28], and having more suppliers more competition [27]. The affordable prices of vaccines could be achieved through tender procedures because vaccine pricing is affected by contract volume and its duration, country, per capita gross domestic product (GDP), and the number of offers received [27,28]. The results indicated that introducing a national immunization program with a 4vHPV vaccine (types 6/11/16/18) for girls aged 11-12 years in Thailand may reduce the incidence and cost associated with HPV 6/11/16/18 related cervical cancer, precancerous lesion and genital warts in Thailand.…”
Section: Discussionmentioning
confidence: 99%